"No pain, no gainz"? Performance and image-enhancing drugs, health effects and information seeking. (3rd September 2017) - Rowe, Rachel; Berger, Israel; Copeland, Jan
Abstract: Background : A range of indicators point to an international increase in the prevalence of performance and image-enhancing drugs (PIEDs) use, predominantly among young men. Attention to PIEDs-related benefits, adverse health effects, information and health service access are needed. Methods : A cross-sectional survey of 605 men who inject PIEDs was conducted at nine primary needle and syringe programme locations across five local health districts in Sydney. Results : Among anabolic–androgenic steroids (AAS) users ( n = 564), anger, rage or irritability (27%, 95%CI: 23.4–30.6) and sexual or genital problems (26.4%, 95%CI: 22.9–30.0) were the most commonly reported adverse health effects. Taking regular, longer breaks between AAS cycles were associated with reduced reports of some adverse effects. Approaching two-thirds of participants had told a doctor about using PIEDs (63.1%, 95%CI: 59.1–67.1). However, as length of time since first injecting PIEDs increased, participants' perceptions of doctors as reliable information sources decreased (rho = −0.10, p = 0.04). Reliance on lay information sources was very common, particularly among people who spoke languages other than English. Conclusions : This study supports providing information on cycle lengths and break periods as part of standard PIEDs-related harm reduction guidelines. Safe injecting and dosage education through peer networks or steroid clinics may be useful strategies.